Evaluation quality as a guarantee of students’ competence-based training - N. . Efremova (Высшее образование в России, 2022)
In accordance with the new requirements of the federal state educational standards of higher education, competences should be considered as the results of the basic educational programs. The universities should provide the assessment of the competence level achieved by student in the learning process. In this article the following topics are covered: approaches to forming of assessment funds as well as internal services, which would organize and conductindependent evaluation procedures of students’ achievements assessment.